Letter: improved parsimony of genetic risk scores for coeliac disease through refined HLA modelling. Issue 6 (18th February 2021) - Erlichster, Michael; Bedo, Justin; Skafidas, Efstratios; Kwan, Patrick; Kowalczyk, Adam; Goudey, Benjamin
Abstract : LINKED CONTENT This article is linked to Sharp et al paper. To view this article, visit https://doi.org/10.1111/apt.15826